Clinical characteristics and immunosuppression management in kidney transplant recipients infected with severe acute respiratory syndrome coronavirus 2 infection - An observational study - Kiruthika Somasundaram; Balasubramaniyan Thoppalan; Vasudevan Chellaiah; R P Senthil Kumar; V Murugesan; S Thirumavalavan (Indian Journal of Transplantation, 2022)
Background: COVID-19 infected kidney transplant patients need specialist care in tailoring their immunosuppression drugs alongside routine care. Methods and Materials: This is an observational data from a single center of 12 kidney transplant recipients (KTR) who were hospitalized with COVID-19 from April 2020 to November 2020. The demographics, COVID treatment including immunosuppressive drug regimen were reviewed. Their graft function during the stay, at the time of discharge, and 30 days after discharge was also reviewed. Results: Of 12 patients included, 83% were male patients. The median age was 37 years and the median time since transplant was 42 months. Common comorbidities were diabetes (50%), hypertension (50%), and cardiovascular disease (8%). Ninety-two percent had triple immunosuppressive regimen whereas 8% were in steroid-free protocol. Fifty percent had mild COVID, 8% had moderate disease, and 41% has severe COVID which was managed with institution-specified protocol. Steroids dose was increased in all patients. Antimetabolite was uniformly withdrawn in all patients irrespective of disease severity. Acute kidney injury was noted in 50% of patients which recovered to baseline at discharge. Graft function at 2 weeks and 30 days after discharge was stabilized close to their baseline value. Mortality was 8%. Conclusion: Reduction of immunosuppression, especially the withdrawal of antimetabolites, was found to be safe without graft rejection in KTRs.